Family Support on Breastfeeding Self-Efficacy Among Pregnant Women - Astuti, Yuni; Sustiwi, Hesti (Universitas Aisyah Pringsewu, 2022)
Breast milk has a complete content of nutrients that benefit the baby. The process of breastfeeding is impacted by the mother's self-efficacy. High maternal confidence in breastfeeding increases breastfeeding success. The self-efficacy of the mother can be influenced by family support. The mother's confidence in breastfeeding could increase with support with care and knowledge. The aim of this study is to evaluate the correlation between family support and self-efficacy in breastfeeding. The cross-sectional research design for descriptive studies. 91 pregnant women who were in their third trimester and had no pregnancy complications made up the sample. A family support survey and the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) instrument were both used as research instruments. Using Spearman's rho correlation, analyze the data. According to this study, 71 persons (78%) fall into the